Customizing supercontinuum generation via on-chip adaptive temporal pulse-splitting. Issue 1 (December 2018) - Wetzel, Benjamin; Kues, Michael; Roztocki, Piotr; Reimer, Christian; Godin, Pierre-Luc; Rowley, Maxwell; Little, Brent; Chu, Sai; Viktorov, Evgeny; Moss, David; Pasquazi, Alessia; Peccianti, Marco; et al.
Abstract Modern optical systems increasingly rely on complex physical processes that require accessible control to meet target performance characteristics. In particular, advanced light sources, sought for, for example, imaging and metrology, are based on nonlinear optical dynamics whose output properties must often finely match application requirements. However, in these systems, the availability of control parameters (e.g., the optical field shape, as well as propagation medium properties) and the means to adjust them in a versatile manner are usually limited. Moreover, numerically finding the optimal parameter set for such complex dynamics is typically computationally intractable. Here, we use an actively controlled photonic chip to prepare and manipulate patterns of femtosecond optical pulses that give access to an enhanced parameter space in the framework of supercontinuum generation. Taking advantage of machine learning concepts, we exploit this tunable access and experimentally demonstrate the customization of nonlinear interactions for tailoring supercontinuum properties. Controlling complex properties of optical systems, like the output of nonlinear light sources, is increasingly important for applications. Here, Wetzel et al. use an actively-controlled photonic chip to prepare patterns of femtosecond laser pulses used for tailoring supercontinuum generation.